The hemlock queen - Whitten, Hannah (Whitten, Hannah. Nightshade crown, 2024)
"The corrupt king August is dead. Prince Bastian has seized the throne and raised Lore--a necromancer and former smuggler--to his right hand side. Together they plan to cut out the rot from the heart of the sainted court and help the people of Dellaire. But not everyone is happy with the changes. The nobles are sowing dissent, the Kyrithean Empire is beating down their door, and Lore's old allies are pulling away. Even Prince Bastian's changed. No longer the hopeful, rakish, charismatic man Lore knows and loves, instead he's reckless, domineering and cold. And something's been whispering in her ear. A voice, dark and haunting, that's telling her there's more to the story than she knows and more to her power than she can even imagine. A truth buried deep that could change everything. With Bastian's coronation fast approaching and enemies whispering on all sides, Lore must figure out how to protect herself, her prince, and her country before they all come crumbling down and whatever dark power has been creeping through the catacombs is unleashed"--